GPR65 inhibits experimental autoimmune encephalomyelitis through CD4+ T cell independent mechanisms that include effects on iNKT cells. Issue 2 (19th December 2017) - Wirasinha, Rushika C; Vijayan, Dipti; Smith, Nicola J; Parnell, Grant P; Swarbrick, Alexander; Brink, Robert; King, Cecile; Stewart, Graeme; Booth, David R; Batten, Marcel
Abstract: The G protein‐coupled receptor 65 ( GPR65 ) gene has been genetically associated with several autoimmune diseases, including multiple sclerosis (MS). GPR65 is predominantly expressed in lymphoid organs and is activated by extracellular protons. In this study, we tested whether GPR65 plays a functional role in demyelinating autoimmune disease. Using a murine model of MS, experimental autoimmune encephalomyelitis (EAE), we found that Gpr65 ‐deficient mice develop exacerbated disease. CD4 + helper T cells are key drivers of EAE pathogenesis, however, Gpr65 deficiency in these cells did not contribute to the observed exacerbated disease. Instead, Gpr65 expression levels were found to be highest on invariant natural killer T (iNKT) cells. EAE severity in Gpr65 ‐deficient mice was normalized in the absence of iNKT cells ( CD1d ‐deficient mice), suggesting that GPR65 signals in iNKT cells are important for suppressing autoimmune disease. These findings provide functional support for the genetic association of GPR65 with MS and demonstrate GPR65 signals suppress autoimmune activity in EAE. Abstract : The G protein‐coupled receptor 65 (GPR65) gene has been genetically associated with multiple sclerosis. This study found that Gpr65‐deficient mice develop exacerbated experimental autoimmune encephalomyelitis (EAE). Regulation of disease was independent of effects on conventional CD4 + helper T cells, but instead relied on regulation of iNKT cells. See also: Short Communication byBarnes and Cyster, News and Commentary byRobert and Mackay .